2013
DOI: 10.4014/jmb.1307.07084
|View full text |Cite
|
Sign up to set email alerts
|

Application of Scale-Up Criterion of Constant Oxygen Mass Transfer Coefficient (kLa) for Production of Itaconic Acid in a 50 L Pilot-Scale Fermentor by Fungal Cells of Aspergillus terreus

Abstract: The scale-up criterion of constant oxygen mass transfer coefficient (kLa) was applied for the production of itaconic acid (IA) in a 50 L pilot-scale fermentor by the fungal cells of Aspergillus terreus. Various operating conditions were examined to collect as many kLa data as possible by adjusting the stirring speed and aeration rate in both 5 L and 50 L fermentor systems. In the fermentations performed with the 5 L fermentor, the highest IA production was obtained under the operating conditions of 200 rpm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Petruccioli et al reported the maximum IA production of 19.8 g/L in 3 L stirred tank bioreactor using corn starch. In a previous study, Shin et al performed fermentation in 5 L stirred tank bioreactor and obtained the highest IA production under the operating condition of 200 rpm and 1.5 vvm. The IA production obtained in bioreactor was lower than that from flask level in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…Petruccioli et al reported the maximum IA production of 19.8 g/L in 3 L stirred tank bioreactor using corn starch. In a previous study, Shin et al performed fermentation in 5 L stirred tank bioreactor and obtained the highest IA production under the operating condition of 200 rpm and 1.5 vvm. The IA production obtained in bioreactor was lower than that from flask level in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…It is also known that the microbial physiology of filamentous fungal cells is significantly influenced by the DO concentration in suspended cultures, and it has been suggested that the critical DO concentration for fungal cells in culture should be greater than around 20% of the saturation DO value [45,46]. In this study, no effort was made to maintain the DO above 20% in order to investigate the effect of DO on enzyme production by the fungus T. reesei MUM 97.53.…”
Section: Influence Of Aeration and Agitation Rates In The Enzymatic Pmentioning
confidence: 98%
“…When the impeller tip speed was 94.2 cm s −1 at a fixed aeration rate of 0.5 vvm, IA production was 3.6 and 1.6 times higher than those in the impeller speed of 62.8 and 125.7 cm s −1 , respectively. Shin et al [81] applied the scale-up criterion of constant oxygen mass transfer coefficient (k L a) for production of IA from glucose in 5 L and 50 L scale fermenters by A. terreus cells. The highest IA production (0.71 g g −1 glucose) was obtained under operating conditions of 200 rpm and 1.5 vvm in a 5 L fermenter, and 180 rpm and 0.5 vvm in a 50 L fermenter.…”
Section: Production Of Itaconic Acid By Aspergillus Terreusmentioning
confidence: 99%